A Vision-Based System for Movement Analysis in Medical Applications: The Example of Parkinson Disease - Spasojević, Sofija; Santos-Victor, José; Ilić, Tihomir; Milanović, Slađan; Potkonjak, Veljko; Rodić, Aleksandar (Computer Vision Systems, 2015)
We present a vision-based approach for analyzing a Parkinson patient’s movements during rehabilitation treatments. We describe therapeutic movements using relevant quantitative measurements, which can be applied both for diagnosis and monitoring of the disease progress. Since our long-term goal is to develop an affordable and portable system, suitable for home usage, we use the Kinect device for data acquisition. All recorded exercises are approved by neurologists and therapists and designed to examine the presence of characteristic symptoms caused by neurological disorders. In this study, we focus on Parkinson’s patients in the early stages of the disease. Our approach underlines relevant rehabilitation measurements and allows to determine which ones are more informative for separating healthy from non-healthy subjects. Finally, we propose the symmetry ratio, well known in motor control, as a novel feature that can be extracted from rehabilitation exercises and used in the decision-making (diagnosis support) and monitoring procedures.